Nuclear Factor E2-Related Factor 2 Mediates Oxidative Stress-Induced Lipid Accumulation in Adipocytes by Increasing Adipogenesis and Decreasing Lipolysis - Sun, Xudong; Li, Xiaobing; Jia, Hongdou; Wang, Heyuan; Shui, Guanghou; Qin, Yonglei; Shu, Xin; Wang, Yazhe; Dong, Jihong; Liu, Guowen; Li, Xinwei (Antioxidants & redox signaling, 2020)
Nuclear factor E2-related factor 2 (Nrf2) is a regulator of cellular oxidative stress and is also involved in lipid metabolism in adipocytes. However, it remains unknown as to whether Nrf2 is the link between oxidative stress and the induction of lipid accumulation in adipocytes. Here, we show that oxidative stress is markedly increased in white adipose tissue from mice with high-fat diet-induced or genetically (ob/ob)-induced obesity and from human subjects with obesity. Notably, in response to oxidative stress, Nrf2 expression and activity were induced, further promoting lipid accumulation in adipocytes and exacerbating the development of obesity. In contrast, Nrf2 ablation alleviated oxidative stress-induced lipid accumulation. Mechanistically, oxidative stress promoted Nrf2 recruitment to the sterol regulatory element binding protein 1 promoter, inducing target gene transcription and subsequent lipogenesis. In addition, Nrf2 mediated oxidative stress-inhibited lipolysis in adipocytes the protein kinase A pathway. Our data provide a novel insight that Nrf2, as a critical signaling node, links oxidative stress to the induction of fat accumulation in adipocytes.